PENDAMPINGAN DAN PELATIHAN DALAM RANGKA PEMANFAATAN WEBSITE DESA SEBAGAI SARANA PROMOSI DESA WISATA DI KECAMATAN JATILAWANG KABUPATEN BANYUMAS (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Rural tourism has developed well in Indonesia. Tourism village management is one sector that continues to receive public attention. The positive impact continues to be felt for the village government and community. However, the development of tourist villages must continue to be balanced with improving quality. One thing that always accompanies information technology. The village websitesite is an inseparable part of the tourist village. The relationship between the two is like a package. However, in reality, village websitesites often lag behind in their progress. Everyone will focus on physical tourist villages without paying attention to increasingly advanced tourism promotion techniques. Assistance for experts who manage village websitesites is very necessary. The aim is to achieve effective and efficient promotion of tourist villages by utilizing existing village websitesites. This assistance is carried out to provide additional insight and skills for village website managers so they can innovate. Assistance with village websitesite management will have an impact on creating interesting and active content, so that it will become a very dynamic and high-quality promotional tool.